Wideband electromagnetic wave absorption by tuning morphology and layer arrangement in Bi-layer absorber based on doped SrFe12O19 nanocomposite powders. Issue 20 (15th October 2022) - Huang, Jian; Huynen, Isabelle; Mehrez, Sadok; Mahariq, Ibrahim; Fayed, Mohamed; Ashour, Ahmed
Abstract: The main parameters for achieving the optimum microwave dissipation performance in bi-layer absorbers are micromorphological characteristics, filler content composition, and layer configurations. In this research, two different doped strontium hexaferrite powders with SrFe10 Al2 O19 (PSrAl) and SrFe10 CoTiO19 (CSrCoTi) chemical formulas were prepared through a solvothermal method. This study aims to identify optimal absorption conditions for bilayer samples by combining different magnetic compositions with varying ferromagnetic resonance and diverse morphologies with different layer arrangements. Single layer absorber samples comprising PSrAl powder with a polygonal pyramidal particle shape displayed dominating dielectric loss behavior and ferromagnetic resonance at about 11.6 GHz, according to the findings. On the other hand, absorber samples containing CSrCoTi powder with crochet ball like particle morphology, exhibit dominant magnetic loss behavior in the studied frequency range, with ferromagnetic resonance around 8.8 GHz. According to the results of bi-layer absorber samples, superior microwave dissipation performance could be achieved by inserting PSrAl powder in the top layer as a matching layer with 0.5 mm thickness and CSrCoTi powder as an absorbing layer 2 mm-thick. For a bi-layer absorber with a 2.5 mm total thickness The EAB (effective absorption bandwidth) is equal to 3.1 GHz at X-band and the minimum reflection loss is equal to −22 dB. The tuning morphology, which improved impedance matching and absorption properties by increasing the wave propagation path in the sample, synergistic effect between two distinct layers, and overlapping of resonance peaks of two components, is credited with this remarkable microwave absorption feature.